Controlled-release kinetics of hydrogen peroxide from dextran-coated calcium peroxide nanoparticles - N N A Nuar; S N A M Jamil; T S Y Choong; I D M Azmi (Materials Research Express, 2025)
In this study, the controlled release kinetics of hydrogen peroxide (H _2 O _2 ) from dextran-coated calcium peroxide nanoparticles (DEX@CaO _2 (DEX) NPs) were investigated. CaO _2 NPs were synthesized and coated with dextran to regulate the release of oxidants (H _2 O _2 ). Controlled-release behavior was examined using a cerium sulfate assay, which revealed that dextran coating significantly moderated H _2 O _2 release. Approximately 52.7% of the total H _2 O _2 content was released gradually within 180 min, compared to the rapid and complete release from the uncoated NPs. Kinetic analysis demonstrated that H _2 O _2 release from DEX@CaO _2 (DEX) NPs followed pseudo-first-order kinetics ( R ^2  = 0.995), indicating diffusion-controlled release through the dextran matrix. The Korsmeyer–Peppas model further indicates an anomalous transport mechanism characterized by both diffusion and polymer relaxation (release exponent n  ≈ 0.6). These findings confirm that dextran coating effectively modulates the release kinetics and provides sustained oxidant availability, which is beneficial for prolonged environmental remediation applications.